Flow cytometry as a new complementary tool to study Coxiella burnetii in cell cultures - Rebbig, Annica; Matthiesen, Svea; Lührmann, Anja; Knittler, Michael R. (Journal of Microbiological Methods, 2018)
Flow cytometry enables the analysis of cells by labeling them with fluorescent probes. We describe a novel flow cytometric approach permitting reliable analysis of Coxiella (C.) burnetii-infected cells. The method quantifies infection-forming units (IFUs) in a dose-dependent manner and allows for the specific detection of infection/replication-competent coxiella in cell cultures.
EVALuna2:36416